(untitled) (Communications in Mathematical Research, 2021)
In this paper, we improve the algorithm and rewrite the function make-Pairing for computing a Gorni-Zampieri pair of a homogeneous polynomial map. As an application, some counterexamples to PLDP (dependence problem for power linear maps) are obtained, including one in the lowest dimension (n = 48) in all such counterexamples one has found up to now.